Systems Mechanobiology: Tension-Inhibited Protein Turnover Is Sufficient to Physically Control Gene Circuits - Dingal, P.C. Dave P. (Biophys J, 2014)
Mechanotransduction pathways convert forces that stress and strain structures within cells into gene expression levels that impact development, homeostasis, and disease. The levels of some key structural proteins in the nucleus, cytoskeleton, or extracellular matrix have been recently reported to scale with tissue- and cell-level forces or mechanical properties such as stiffness, and so the mathematics of mechanotransduction becomes important to understand. Here, we show that if a given structural protein positively regulates its own gene expression, then stresses need only inhibit degradation of that protein to achieve stable, mechanosensitive gene expression. This basic use-it-or-lose-it module is illustrated by application to meshworks of nuclear lamin A, minifilaments of myosin II, and extracellular matrix collagen fibers—all of which possess filamentous coiled-coil/supercoiled structures. Past experiments not only suggest that tension suppresses protein degradation mediated and/or initiated by various enzymes but also that transcript levels vary with protein levels because key transcription factors are regulated by these structural proteins. Coupling between modules occurs within single cells and between cells in tissue, as illustrated during embryonic heart development where cardiac fibroblasts make collagen that cardiomyocytes contract. With few additional assumptions, the basic module has sufficient physics to control key structural genes in both development and disease.